Grapevines escaping trunk diseases in New Zealand vineyards have a distinct microbiome structure - Adejoro, Damola O.; Jones, E. Eirian; Ridgway, Hayley J.; Mundy, Dion C.; Vanga, Bhanupratap R.; Bulman, Simon R. (Frontiers in Microbiology, 2023)
Grapevine trunk diseases (GTDs) are a substantial challenge to viticulture, especially with a lack of available control measures. The lack of approved fungicides necessitates the exploration of alternative controls. One promising approach is the investigation of disease escape plants, which remain healthy under high disease pressure, likely due to their microbiome function. This study explored the microbiome of grapevines with the disease escape phenotype. DNA metabarcoding of the ribosomal internal transcribed spacer 1 (ITS1) and 16S ribosomal RNA gene was applied to trunk tissues of GTD escape and adjacent diseased vines. Our findings showed that the GTD escape vines had a significantly different microbiome compared with diseased vines. The GTD escape vines consistently harbored a higher relative abundance of the bacterial taxa Pseudomonas and Hymenobacter. Among fungi, Aureobasidium and Rhodotorula were differentially associated with GTD escape vines, while the GTD pathogen, Eutypa lata, was associated with the diseased vines. This is the first report of the link between the GTD escape phenotype and the grapevine microbiome. This is a provisional file, not the final typeset article enhance the health of the plant by inducing innate plant defense systems, improving tolerance to stress conditions, promoting plant growth, and/or directly inhibiting pathogen growth by producing antimicrobial compounds (